“Historical Mode”. Heritage and Revival in Contemporary Fashion - Sofia Gnoli (ZoneModa Journal, 2023)
The article explores the links between fashion and the past in contemporary times, the love of revival, the taste for vintage and the importance of a brand's cultural heritage. All elements that today, in the midst of globalisation, have become increasingly important. Brand heritage is a fundamental aspect of a brand's identity, it represents what a brand is now seen through the lens of its own history. This yearning for the appreciation of one's roots is one of the priorities of the big luxury holding companies which, for 25 years now, have tirelessly continued their climb up the ranks of the brands with the most illustrious history.